The Lynching and Rebirth of Ned Buntline: Rogue Authorship during the American Literary Renaissance - Metzler Sawin, Mark (Text Matters: A Journal of Literature, Theory and Culture, 2019)
Though largely unknown today, “Ned Buntline” (Edward Zane Carroll Judson) was one of the most influential authors of 19th-century America. He published over 170 novels, edited multiple popular and political publications, and helped pioneer the seafaring adventure, city mystery and Western genres. It was his pirate tales that Tom Sawyer constantly reenacted, his “Bowery B’hoys” that came to define the distinctive slang and swagger of urban American characters, and his novels and plays that turned an unknown scout into Buffalo Bill, King of the Border Men. But before “Ned Buntline” became a mainstay of the popular press, he had been on his way to becoming one of the nation’s highbrow literary elites. He was praised by the leading critics, edited an important literary journal, and his stories appeared in the era’s most prestigious publications. This study examines how and why “Ned Buntline” moved from prestigious to popular authorship and argues that the transformation was precipitated by one very specific event: in 1846, Edward Z. C. Judson was lynched. A close examination of Judson’s life, writing, and the coverage of him in the newspapers of the day (including the remarkable story of how he survived a lynching) demonstrates that the same issues that led to his lynching also led to his rebirth as a new kind of American author.